Integrating a Group-Based, Early Childhood Parenting Intervention Into Primary Health Care Services in Rural Bangladesh: A Cluster-Randomized Controlled Trial - Mehrin, Syeda Fardina; Hasan, Mohammed Imrul; Tofail, Fahmida; Shiraji, Shamima; Ridout, Deborah; Grantham-McGregor, Sally; Hamadani, Jena D.; Baker-Henningham, Helen (Frontiers in Pediatrics, 2022)
Background: Over 250 million children globally do not reach their developmental potential. We tested whether integrating a group-based, early childhood parenting programme into government healthcare clinics improved children’s development, growth, and behaviour. Methods: We conducted a cluster-randomised controlled trial in 40 community clinics in the Kishorganj district of Bangladesh. We randomly assigned clinics (1:1) to deliver a group-based parenting interventions or to a comparison group that received no intervention. Participants were children aged 5-24 months, with weight-for-age z-score of ≤ -1.5 SDs of the WHO standards, living within a thirty-minute walking distance from the clinic (n=419 intervention, 366 control). Government health staff facilitated parenting sessions in the clinic with groups of four mother/child dyads fortnightly for one year as part of their routine duties. Primary outcomes measured at baseline and endline were child development measured using the Bayley scales, child behaviours during the test, and growth and were. The trial is registered at ClinicalTrials.gov, NCT02208531 Findings: 91% of children were tested at endline (396 intervention, 319 control). Multilevel analyses showed significant benefits of intervention to child cognition (effect size 0.85 SDs, 95% CI: 0.59, 1.11), language (0.69 SDs, 0.43, 0.94), and motor development (0.52 SDs, 0.31, 0.73), and to child behaviours during the test (ranging from 0.36 SDs, 0.14, 0.58, to 0.53 SDs, 0.35, 0.71). There were no significant effects on growth. Conclusion: A scalable parenting intervention, integrated into existing government health services and implemented by government health staff, led to significant benefits to child development and behaviour.